STRATEGI PEMASARAN CV. KARYATAMA DALAM MENINGKATKAN VOLUME PENJUALAN - Deasy Chrisnia Natalia; Grace Novaline Simanjuntak (Jurnal VOK@SINDO, 2020)
Abstract : The Marketing Strategy of CV Karyatama in Increasing Sales Volume. In running its business, each company will use a marketing strategy. Marketing strategy is an effort to market products, both goods and services, using a pattern or a certain way, so in a certain long term, the sales volume can be obtained. There are various kinds of marketing strategies, one of them is the Marketing Mix strategy. The variables of the Marketing Mix are Product, Price, Promotion, and Place. CV Karyatama, uses a Marketing Mix to run its business. The purpose of this final project is to determine the marketing strategy of CV Karyatama in increasing sales volume. The method used in this final project is descriptive method. The result of this final project is, the implementation of the marketing strategy at CV Karyatama, has increased the sales volume.